Insights into the habitat associations, phylogeny, and diet of Pipistrellus maderensis in Porto Santo, northeastern Macaronesia - Nóbrega, EK; Toshkova, N; Gonçalves, A; Reis, A; Soto, EJ; Ruiz, SP; Mata, VA; Rato, C; Rocha, R (Copernicus Publications, 2023)
Around 60 % of all bat species occur in islands, and nearly one in four is an insular endemic. Bats are often the only native terrestrial mammals in oceanic islands, and despite increasing anthropogenic pressures, little is known about the distribution, natural history, and population status of most insular bat populations. The sub-tropical archipelago of Madeira is composed of the volcanic islands of Madeira, Porto Santo, and Desertas and is home to the Macaronesian endemic Pipistrellus maderensis, to the endemic subspecies Nyctalus leisleri verrucosus, and to Plecotus austriacus. Pipistrellus maderensis is known to both Madeira and Porto Santo, whereas the other two species have only been recorded in the former. However, no bats have been recorded in Porto Santo for over 15 years, raising fears that bats are probably extinct in the island. In July 2021, we conducted an island-wide acoustic survey using AudioMoth passive acoustic recorders, leading to the detection of Pipistrellus maderensis in 28 out of the 46 sampling sites (60 %). The species' activity was strongly associated with artificial water sources, and genetic samples from six captured individuals revealed that the populations of Pipistrellus maderensis in Porto Santo and Madeira have a close phylogenetic affinity. Furthermore, using DNA metabarcoding, we found that the species feeds on a wide variety of insects, including several economically important pest species and disease vectors. These findings emphasise the need to target more conservation and research efforts towards extant island bat populations and the potential ecosystem services they provide.